“Semar Gugat” dalam Telaah Tokoh: Sebuah Model Pemaknaan Naskah Drama - Muhammad Ismail Nasution (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
This paper analyses the characters involvde in “Semar Guga Play” in relation to the plot of the story. Thus, the analysis of character (s) in a drama text (script) cannot be separated from the analysis of the element of plot of the story. In other words both elements – characters and plot – support each other. The research method is qualitative design in which data is analyzed inductive and descriptively. Furthermore, the analysis of setting is also inseparable with the elementsof plot and character. In conclusion “Semar Gugat” does not only criticize phenomena of social condition, but also deconstructs the Javanese’s view towards Semar and Arjuna" wayang. Keywords: drama or theater, drama script, characterization, plot and value